Analysis of The Influence of Good Corporate Governance and Financial Health Ratio on Banking Performance - Aloysius Harry Mukti; Tamara Rahmawati (Universitas Padjadjaran, 2022)
This study aims to examine the effect of good corporate governance and financial health ratios as measured by CAR NPL and BOPO on banking performance. This study used a sample of 93 and the objects in this study were conventional banking companies listed IDX 2017-2019. This study uses secondary data with a sample selection method, namely purposive sampling. This study uses 5 data analysis methods, namely descriptive statistics, classical assumption test, hypothesis test, f test, and partial test / t. This study proves that good corporate governance has no effect on banking performance, financial health ratios as measured by CAR have no effect on banking performance, financial health ratios as measured by NPL have no effect on banking performance and financial health ratios as measured by BOPO have a negative effect on banking performance.